2004
DOI: 10.1212/wnl.62.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Normal intelligence in children with prenatal exposure to carbamazepine

Abstract: Carbamazepine monotherapy with maternal serum levels within the reference range does not impair intelligence in prenatally exposed offspring. Exposures to polytherapy and to valproate during pregnancy were associated with significantly reduced verbal intelligence. The independent effects of valproate remain unconfirmed because the results were confounded by low maternal education and polytherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
268
5
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 271 publications
(318 citation statements)
references
References 19 publications
27
268
5
15
Order By: Relevance
“…Pooled data from two prospective population-based studies [55,56] showed a 1.9% (2/105) incidence of mental deficiency in carbamazepine monotherapy-exposed children of WWE. One of the two children had West syndrome in infancy as a possible etiology.…”
Section: Carbamazepinementioning
confidence: 99%
See 4 more Smart Citations
“…Pooled data from two prospective population-based studies [55,56] showed a 1.9% (2/105) incidence of mental deficiency in carbamazepine monotherapy-exposed children of WWE. One of the two children had West syndrome in infancy as a possible etiology.…”
Section: Carbamazepinementioning
confidence: 99%
“…Carbamazepine monotherapy was the most common AED exposure in two recent prospective, controlled, population-based studies [56,57] with blinded evaluation of outcome. These studies included approximately 50% of the population of children born to WWE in their catchment areas: carbamazepine monotherapy exposures numbered 35 in the former and 86 in the latter study.…”
Section: Carbamazepinementioning
confidence: 99%
See 3 more Smart Citations